Weapon Ownership and the Willingness to Respond to Threats with Violence: The United States and Japan - Friday, Paul C.; Dussich, John P.; Okada, Takayuki; Yamagami, Akira (International journal of offender therapy and comparative criminology, 2000)
Using data collected in Tokyo and Mito, Japan, and in Charlotte, North Carolina, the impact of weapons on the willingness to use violence in a variety of defined scenarios was analyzed. The American sample was twice as likely as the Japanese sample to say they would use a weapon when confronted by a stranger, by a known acquaintance, or if someone illegally entered their homes. The major finding is that the stated willingness to use a weapon is significantly tied to whether one owned a weapon for personal safety and being male in both countries. Logistic regression shows the likelihood of responding to a threat by physical force to be twice as great in Japan and nearly eight times as great in Charlotte if the respondent owned a weapon. These data support the thesis of a weapons effect that influences one's definition of the situation